The alterations in event-related potential responses to pain empathy in breast cancer survivors treated with chemotherapy - Li, Wen; Lv, Yue; Duan, Xu; Cheng, Guo; Yao, Senbang; Yu, Sheng; Tang, Lingxue; Cheng, Huaidong (Frontiers in Psychology, 2022)
Background: Previous founding indicated that breast cancer patients often have empathy and other cognitive dysfunction during or after chemotherapy. However, the manifestations and possible neuro-electrophysiological mechanism of pain empathy impairment in breast cancer patients after chemotherapy were still unknown. Objective: The current study aimed to investigate the potential correlations between pain empathy impairment and event-related potentials (ERP) in breast cancer patients undergoing chemotherapy. Methods: Twenty-two breast cancer patients were evaluated on neuropsychological test and pain empathy paradigm before and after chemotherapy, containing Chinese version of Interpersonal Reactivity Index (IRI-C), while recording of ERP data. Results: The empathic concern scores were lower and personal distress scores were higher on IRI-C task in compared with these before chemotherapy (t=3.039, p<0.01; t=－2.324, p<0.05, respectively). Meanwhile, the accuracy rates were lower than these before chemotherapy for both pain and laterality tasks on pain empathy paradigm (F=5.099, P = 0.035). However, the response time was no significant differences before and after chemotherapy (F=0.543, P=0.469). Further, the amplitude of N1 component was significantly increased (F=38.091, P < 0.001) and the amplitude of P2 component was significantly decreased (F=15.046, P = 0.001) in the subsequent ERP study. Linear mixed effect model was used to analyze the correlation, the average amplitude of N1 and P2 were positively correlated with the accuracy rates in laterality tasks (r=1.765, r=1.125, respectively, P<0.05). Conclusion: The results indicated that pain empathy impairment was performed in chemotherapeutic breast cancer patients, which was possibly correlated to the changes of N1 and P2 components in ERP. These findings provide neuro-electrophysiological information about chemo-brain in breast cancer patients.